2010
DOI: 10.1177/0956797609358570
|View full text |Cite
|
Sign up to set email alerts
|

From Statistics to Meaning

Abstract: Infants are highly sensitive to statistical patterns in their auditory language input that mark word categories (e.g., noun and verb). However, it is unknown whether experience with these cues facilitates the acquisition of semantic properties of word categories. In a study testing this hypothesis, infants first listened to an artificial language in which word categories were reliably distinguished by statistical cues (experimental group) or in which these properties did not cue category membership (control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 20 publications
2
77
1
1
Order By: Relevance
“…Pairing language categories with objects can help learners differentiate sounds (Yeung & Werker, 2009), learn phonological rules (Frank et al, 2009;Thiessen, 2012;van den Bos et al, 2012), and segment words (at least in adulthood; Thiessen, 2010). Statistical information like transitional probabilities (Graf Estes et al, 2007) or distributional cues (Lany & Saffran, 2010;Thiessen, 2007) can facilitate word learning. Christiansen, (2013a;2013b) has argued that cue redundancy is a crucial component of language.…”
Section: Implications Of the Results For Our Understanding Of Early Wmentioning
confidence: 99%
“…Pairing language categories with objects can help learners differentiate sounds (Yeung & Werker, 2009), learn phonological rules (Frank et al, 2009;Thiessen, 2012;van den Bos et al, 2012), and segment words (at least in adulthood; Thiessen, 2010). Statistical information like transitional probabilities (Graf Estes et al, 2007) or distributional cues (Lany & Saffran, 2010;Thiessen, 2007) can facilitate word learning. Christiansen, (2013a;2013b) has argued that cue redundancy is a crucial component of language.…”
Section: Implications Of the Results For Our Understanding Of Early Wmentioning
confidence: 99%
“…Determiners may facilitate word learning by providing information about nouns as a lexical category (Lany & Saffran, 2010). In grammatical input, determiners often precede nouns; in fact, the is immediately followed by a noun up to 93% of the time in speech directed to typically developing young children (Thorpe & Fernald, 2006).…”
Section: The Current Studymentioning
confidence: 99%
“…Moreover, infants are able map the outputs of statistical learning (e.g. potential word forms) to referents and to lexical categories, without explicit instruction or reinforcement [37][38][39], consistent with statistical learning having a role to play in natural language development (for a review, see [40]). Building on this work examining statistical learning and language learning in typical development, Evans et al [41] asked whether children with LI showed differences in statistical learning, relative to age-matched controls.…”
Section: Lexical Learning In Language Impairmentmentioning
confidence: 99%